2017
DOI: 10.1016/j.jcrs.2017.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Anterior segment approach for the surgical management of aqueous misdirection syndrome

Abstract: We describe the surgical management of the aqueous misdirection syndrome through clear corneal incisions. A 20-gauge microvitreoretinal blade is used to create 2 side-port incisions. The same blade is inserted through the cornea and the iris for the main incision; it is then directed toward the center of the eyeball, passing through the zonular fibers to the vitreous cavity behind the pupil. Irrigation is delivered to the anterior chamber, the vitrector is placed in the vitreous cavity, and vitrectomy is perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…If both medical and laser treatment fail, pars plana vitrectomy is thought to prevent aqueous humour from accumulating in the vitreous cavity and the hyaloido‐zonula‐iridectomy to ensure the communication between the anterior chamber and the vitreous cavity. A few studies have combined the vitrectomy and HZI with the removal of the lens and implantation of IOL if the patients were phakic (Debrouwere et al 2012; Dervenis, Mikropoulou & Dervenis 2017; Tang, Du & Li 2018; Raj et al 2019). We cannot determine whether vitrectomy with HZI combined with phacoemulsification gives a better result than vitrectomy with HZI alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If both medical and laser treatment fail, pars plana vitrectomy is thought to prevent aqueous humour from accumulating in the vitreous cavity and the hyaloido‐zonula‐iridectomy to ensure the communication between the anterior chamber and the vitreous cavity. A few studies have combined the vitrectomy and HZI with the removal of the lens and implantation of IOL if the patients were phakic (Debrouwere et al 2012; Dervenis, Mikropoulou & Dervenis 2017; Tang, Du & Li 2018; Raj et al 2019). We cannot determine whether vitrectomy with HZI combined with phacoemulsification gives a better result than vitrectomy with HZI alone.…”
Section: Discussionmentioning
confidence: 99%
“…If the anterior approach is chosen, the HZI from the anterior chamber is performed, followed by an anterior vitrectomy through the HZI (Table 1). Several studies have described low relapse rates with this approach (Lois, Wong & Groenewald 2001; Tsai & Tseng 2004; Basgil Pasaoglu et al 2012; Madgula & Anand 2014; Żarnowski et al 2014; A Khan 2016; Dervenis, Mikropoulou & Dervenis 2017; Pakravan et al 2018; Wang, Du & Tang 2018; Faisal et al 2019; Ray & Malhotra 2019). One study, however, reported relapse in 4 out of 10 eyes (Madgula & Anand 2014).…”
Section: Methodsmentioning
confidence: 99%